2013
DOI: 10.1155/2013/408734
|View full text |Cite
|
Sign up to set email alerts
|

Action Mechanism ofGinkgo bilobaLeaf Extract Intervened by Exercise Therapy in Treatment of Benign Prostate Hyperplasia

Abstract: Benign prostatic hyperplasia (BPH), an imbalance between androgen/estrogen, overexpression of stromal, and epithelial growth factors associated with chronic inflammation, has become an atypical direct cause of mortality of aged male diseases. Ginkgo possesses anti-inflammatory, blood flow-enhancing, and free radical scavenging effects. Considering strenuous exercise can reduce BPH risks, we hypothesize Ginkgo + exercise (Ginkgo + Ex) could be beneficial to BPH. To verify this, rat BPH model was induced by s.c.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The results presented here are controversial; we demonstrated that the body weight severely decreased, suggesting pathological changes in the STZ-induced DM, testosterone-induced BPH, and innate human DM models. Previously, we demonstrated that EX was able to suppress the prostatic inflammation in BPH [ 7 ]. A similar result regarding the DM group was reported by Belotto et al [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results presented here are controversial; we demonstrated that the body weight severely decreased, suggesting pathological changes in the STZ-induced DM, testosterone-induced BPH, and innate human DM models. Previously, we demonstrated that EX was able to suppress the prostatic inflammation in BPH [ 7 ]. A similar result regarding the DM group was reported by Belotto et al [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combined effect of DM + BPH + EX is still unclear. Previously, we proved EX to alleviate BPH [ 7 ]. In this work, we demonstrated that EX not only apparently alleviated the hyperplastic epithelial and stromal growth, inhibiting collagen deposition in BPH (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the undesirable secondary effects and the longer administration time of conventional drug treatments [32], several researchers have proposed other agents for the prostatic inflammation treatment, such as modulators of the immune system. For example, Ginkgo biloba leaf extract decreased the signs of inflammation associated with BPH in prostatic tissue [33]. Also, a clinical report on metastatic prostate cancer suggested a correlation between DLE treatment and patient survival or remission [12].…”
Section: Discussionmentioning
confidence: 99%